El objetivo del estudio fue evaluar el efecto de dietas con alta concentración de Saccharomyces cerevisiae sobre la proliferación de hemocitos en camarones Cryphiops caementarius machos. Los camarones (5.3 ± 1.2 cm de longitud total y 7.4 ± 2.9 g de peso - Cabrera P., Elizabeth (2019)
The aim of this study was to evaluate the effect of diets with high concentration of Saccharomyces cerevisiae on the proliferation of hemocytes in male shrimp Cryphiops caementarius. The shrimp (5.3 ± 1.2 cm of total length and 7.4 ± 2.9 g of total weight) were collected from the Pativilca River (Peru). Each shrimp was kept in a container installed inside the aquarium (six shrimp per aquarium). A control diet (3% yeast) and three experimental diets (6, 9 and 12% yeast) were used with two repetitions per treatment during 28 days of culture. The total number of hemocytes was higher (p<0.05) with 6% yeast (134.75 x 105 cells/ml), as well as the number of granulocytes (31.44 x 105 cells/ml) and semigranulocytes (102.44 x 105 cells/ml). The number of hyalinocytes decreased in all treatments and remained between 0.31 and 1.56 x 105 cells/ml. The number of atypical hemocytes remained low in all treatments and without differences with the baseline (0.31 x 105 cells/ml). The diet with 6% yeast increased (p<0.05) the total number of hemocytes and the granulocyte and semigranulocyte hemocytes in C. caementarius male shrimps. In contrast, diets with 9 and 12% of yeast affected (p<0.05) the proliferation of total and differential hemocytes.